Cytotoxicity and cellular imaging of quantum dots protected by polyelectrolyte - Hai-Yan Hu; Xing-Ru Dou; Zong-Lin Jiang; Jian-Hua Tang; Lian Xie; Hong-Ping Xie (Elsevier, 2012)
The nanocomposites of poly-diallyldimethylammonium chloride (PDADMAC) and CdTe quantum dots (QDs) (i.e. QDs-PDADMAC nanocomposites) have been prepared based on electrostatic interaction and their fluorescence stability in aqueous solution has been investigated. MTT method (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide method) was used to study their cytotoxicity and A549 lung cancer cell as a model cell was also used to evaluate their cellular imaging. It was shown that the fluorescence stability of QDs-PDADMAC nanocomposites was much better than that of bare QDs both in aqueous solution and cell. Meanwhile, QDs-PDADMAC nanocomposites display very low cytotoxicity in the low concentrations and better staining ability compared with QDs. QDs-PDADMAC nanocomposites will have great advantage on the cell analysis detection and imaging. Keywords: CdTe quantum dots, Poly-diallyldimethylammonium chloride, Nanocomposites, Cytotoxicity, Cellular imaging